Residual free calcium is not responsible for facilitation of neurotransmitter release. - Blundon, J A (1993)
An increase in internal free calcium ([Ca2+]i) in the presynaptic terminal is often assumed to directly produce facilitation of neurotransmitter release. Using a Ca(2+)-activated potassium conductance as a bioassay for free [Ca2+]i in the presynaptic terminal of the crayfish (Procambarus clarkii) opener neuromuscular junction, we now demonstrate that free [Ca2+]i has a decay time constant (tau) of 1-4 msec, whereas facilitation of neurotransmitter release has a decay tau of 7-43 msec. In addition, facilitation of neurotransmitter release can be markedly different at times when free [Ca2+]i values and presynaptic membrane voltages are equal. We conclude that free [Ca2+]i in the presynaptic terminal is not directly responsible for facilitation of neurotransmitter release. Our data suggest that facilitation results from bound Ca2+ or some long-lived consequence of bound Ca2+.